Technical project for drilling a production well in terms of Bakr oil field (Egypt) - Khalil, Omar Asaad Mohamed (НТУ "Дніпровська політехніка", 2022)
The purpose of the study is to design a well at the Bakr field
Research tools are literature analysis and theoretical research. The paper is compiled in accordance with the requirements of the guidelines. It contains information about the area of drilling, geological structure and characteristics of productive horizons. In the design part, the issues of well construction are resolved: the well structure has been designed, the equipment for the drilling rig, the rock cutting tool, the drilling and cementing technology have been selected. Measures have been developed to improve the quality of drilling fluids during preparation. Safety precautions are given when drilling wells. The issues of subsoil and environmental protection are highlighted. The estimate of well drilling has been substantiated
Keywords: PRODUCTION WELL, WELL, DRILL BITS, DRILLING FLUID, DRILLING TECHNOLOGY